High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes - Ivanov Yu. F. Yuriy Fedorovich; Laskovnev A. P.; Teresov A. D.; Cherenda N. N. Nikolay Nikolaevich; Uglov V. V. Vladimir Vasilievich; Petrikova E. A.; Astashinskaya M. V.; Koval N. N. (2015, 2015)
Title screen